2022
DOI: 10.3389/fpubh.2022.901976
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Hearing Aids-Related Videos on TikTok

Abstract: Hearing aids are effective at improving listening ability and health-related quality of life. Recently, we observed that there are many hearing aids-related videos published on TikTok. However, the quality of the information they offer remains unstudied. This study aimed to evaluate the information quality of hearing aids videos on TikTok. We collected a sample of 155 hearing aids-related videos in Chinese and extracted the basic information. First, we identified the source of each video. Two independent rater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Our results are generally in concordance with previous studies evaluating the quality of TikTok videos for dissemination of healthcare information. 9 , 31 , 32 Our study reveals worse scoring metrics than those reported by Jang et al, who found a total DISCERN score of 33.60 for the videos related to scoliosis exercises on TikTok. However, other studies have found TikTok to be a suitable outlet for the distribution of medical information for other fields outside of orthopaedics such as diabetes (total DISCERN score of 40 to 51), 9 chronic obstructive pulmonary disease (total DISCERN score of 57 to 67), 10 and medical abortion (modified DISCERN score of 2.8 of 5).…”
Section: Discussioncontrasting
confidence: 89%
“…Our results are generally in concordance with previous studies evaluating the quality of TikTok videos for dissemination of healthcare information. 9 , 31 , 32 Our study reveals worse scoring metrics than those reported by Jang et al, who found a total DISCERN score of 33.60 for the videos related to scoliosis exercises on TikTok. However, other studies have found TikTok to be a suitable outlet for the distribution of medical information for other fields outside of orthopaedics such as diabetes (total DISCERN score of 40 to 51), 9 chronic obstructive pulmonary disease (total DISCERN score of 57 to 67), 10 and medical abortion (modified DISCERN score of 2.8 of 5).…”
Section: Discussioncontrasting
confidence: 89%
“…25 The Patient Education Materials Assessment Tool for Audiovisual Materials is a method for evaluating online audio-visual patient material, and has been applied to videos relating to otolaryngology issues and conditions such as hearing aid quality, endoscopic sinus surgery and sinusitis. 11,26,27 However, such studies reported a poor Patient Education Materials Assessment Tool score that fell well below the recommended threshold of 70 per cent. 10 In comparison, our study demonstrated that the Patient Education Materials Assessment Tool score for epistaxis first-aid management videos on YouTube surpassed the minimum standard threshold, with mean understandability and actionability scores of 76 per cent and 89 per cent, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous research on the quality and reliability of health‐related videos on TikTok. In studies by John et al, Chen et al, and Kong et al, tonsillectomy, hearing aid, and diabetes‐related TikTok videos created by physicians had higher DISCERN scores than those made by nonphysicians 24–26 . A study by Om et al on aesthetic surgery procedure, TikTok videos found that educational videos had the highest average DISCERN scores 16 .…”
Section: Discussionmentioning
confidence: 99%